KAJIAN ANALISIS USAHATANI PENGGUNAAN PUPUK ORGANIK NON KOMERSIAL TERHADAP HASIL DAN PENDAPATAN PETANI PADI - Valeriana Darwis (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Policy of providing chemical fertilizers at low prices through the subsidies continue to increase every year, causing inefficient use of fertilizers by farmers and in turn lower the productivity of the land. The study was conducted in the province of West  Java and Central Java in 2012, aims to (1) evaluate the costs and revenues of non commercial organic fertilizer and (2) analyzing farm income and the factors that affect  rice  production.  Total  farmer  respondents  interviewed  60  farmers  with  30 farmers  who  earn  program  Organic  Fertilizer  Processing  Unit  (UPPO)  and  30 farmers who do not follow the program UPPO. To determine the effect of the use of organic fertilizers used in rice cultivation model of linear production function CobbDouglas and financial analysis or benefit cost ratio (B/C). The results showed good organic fertilizer production enterprises in the form of solid or liquid organic fertilizer is quite profitable. Farmers earn net income of  Rp.  83-112 per kg of organic fertilizer in 6 weeks. The amount of chemical fertilizers used on semi-organic rice farming is reduced  by  approximately  50%  of  the  amount  of  chemical  fertilizers  used  in  nonorganic farming. The use of labor in  semi-rice  organic  farming  is  higher than nonorganic farming, especially at  the  stage of cultivation and weeding. R/C ratio of semiorganic rice farming is greater than non-organic rice which indicates that the semiorganic rice farming more profitable financially.